2017
DOI: 10.1016/j.actamat.2017.08.066
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale modeling of the anisotropic electrical conductivity of architectured and nanostructured Cu-Nb composite wires and experimental comparison

Abstract: International audienceNanostructured and architectured copper niobium composite wires are excellent candidates for the generation of intense pulsed magnetic fields (> 90T) as they combine both high electrical conductivity and high strength. Multi-scaled Cu-Nb wires can be fabricated by accumulative drawing and bundling (a severe plastic deformation technique), leading to a multiscale, architectured and nanostructured microstructure providing a unique set of properties. This work presents a comprehensive multis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…(1) Even though grain size effect has been taken into account in this work for Cu-Nb Filamentary wires N = 85 2 , its impact on effective material behavior is not significant, as the volume fraction of fine Cu components is rather small ( 15%). In contrast, other types of Cu-Nb wires, such as the Filamentary wires N = 85 3 (see Gu et al (2017b) for the material descriptions), exhibit a higher volume fraction of ultra-fine Cu grains. The importance of size effects will be studied by multiscale modeling for these Cu-Nb wires.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Even though grain size effect has been taken into account in this work for Cu-Nb Filamentary wires N = 85 2 , its impact on effective material behavior is not significant, as the volume fraction of fine Cu components is rather small ( 15%). In contrast, other types of Cu-Nb wires, such as the Filamentary wires N = 85 3 (see Gu et al (2017b) for the material descriptions), exhibit a higher volume fraction of ultra-fine Cu grains. The importance of size effects will be studied by multiscale modeling for these Cu-Nb wires.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the Cu-Nb nanocomposite wires and laminates have focused on textures and their evolution (Lim and Rollett, 2009;Dubois, 2010;Lee et al, 2012;Hansen et al, 2013;Medy, 2016), elasticity (Gu et al, 2017a), dislocation glide (Thilly et al, 2001;Misra and Hoagland, 2007), grain size dependent yield stress/yield criterion (Misra and Hoagland, 2007;Thilly et al, 2009;Nizolek et al, 2015), Bauschinger effect (Thilly et al, 2007;Badinier et al, 2014), hardness (Thilly et al, 2002), ultimate tensile strength (Vidal et al, 2007), Cu-Nb interfaces (Mayeur et al, 2013(Mayeur et al, , 2015Beyerlein et al, 2014), and thermal stability and internal stresses (Vidal, 2006;Dubois et al, 2010;Beyerlein et al, 2014). The electrical behavior of Cu-Nb composites was studied by Gu et al (2015Gu et al ( , 2017b.…”
Section: Introductionmentioning
confidence: 99%
“…The ADB process results in a multi-scale Cu matrix containing continuous parallel Nb fibers with a maximum number of up to 85 4 (N = 85 4 , determined by the number of drawing steps) and with diameters varying in the range of 10 nm to 500 µm. Four different types of specimens were prepared after each pass of the first four ADB process, with N = 85, 85 2 , 85 3 , and 85 4 . These samples were designated by the number of Nb fibers.…”
Section: Methodsmentioning
confidence: 99%
“…Over the past two decades, Cu-Nb microcomposites have been widely used in defense, aerospace, and magnetic applications for their excellent combination of mechanical properties, high conductivity, and thermal stability [1][2][3][4]. Several techniques have been used to fabricate these materials, including accumulative drawing and bonding (ADB) [5,6], melt and deform [7,8], accumulative roll bonding (ARB) [9][10][11], and magnetron sputtering [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] For example, it was reported that the tensile strength of an Al/Sn multilayer composite was about 2.2 times higher than for pure Al. [23] In a recent study, Cu/Nb nanostructured composites not only exhibited high conductivity [24] and high strength [15] but also held great promise for applications requiring resistance to high-energy radiation damage, [25,26] plastic deformation, [20] and exposure at elevated temperatures. This combination of properties makes multilayer composites attractive for a range of applications.…”
Section: Introductionmentioning
confidence: 99%